Recent advances in metallurgy and design of rotary endodontic instruments: a review - Palekar, Aparna; Vajpayee, Akhilesh; Biradar, Basawaraj (International Journal of Dental Materials, 2020)
A variety of instruments are available for the extirpation of the pulp and the instrumentation and preparation of the root canal. Recently, nickel-titanium (NiTi) alloy is utilised for the manufacturing of endodontic instruments. Compared to other metals, these alloys are highly flexible, which significantly enhances ease of canal shaping. This review article gives an account in the advances of NiTi endodontic instruments with an emphasis on metallurgical, mechanical properties, the design features of each generation with a special focus on the latest generations of NiTi instruments.